The study of the concept of medical literacy and approaches to its assessment: uk. - Volkova, A. V.; Kovtun, Ye. Yu. (Social Pharmacy in Health Care, 2021)
According to the Ministry of Health of Ukraine, almost 70% of the population self-medicates without seeking medical help. Therefore, the correct perception of medical and pharmaceutical information determines the correct use of drugs, their effectiveness and safety for the population. Aim. To analyze global approaches to determining medical literacy and assessing its level in the world. Materials and methods. The research materials were publications in scientific periodicals, monographs, materials of official websites of world organizations and databases, such as JMIR, PubMed, ISI Web of Science, Academic Search Premier and Allied Health Literature. During the study the methods of the content analysis, historical, system-analytical, generalization were used. Results. The authors have reviewed the literature on the concept of “medical literacy” and approaches to its assessment. The chronological periods of formation of the concept of “medical literacy” have been generalized. The following tests have been identified as key tools for assessing medical literacy in most studies: TOFHLA, REALM, NVS, and HLS-EU-Q47. Based on the results of the content analysis of the existing approaches in assessing the level of medical literacy of the population, the main indicators proposed for evaluation have been generalized, and the advantages and disadvantages of these tests have been considered. Conclusions. The analysis conducted has shown that a promising study is the development of universal and optimal tools for assessing the level of medical literacy, as well as the definition of the concept of “pharmaceutical literacy” with its components, the development of methods for assessing pharmaceutical literacy, the implementation and evaluation of practices to improve medical and pharmaceutical literacy. Key words: the concept of “medical literacy” and “pharmaceutical literacy”, approaches of health literacy assessment.